An acid trip activates protumoral macrophages to promote hepatocellular carcinoma malignancy - Nicola Graham; Jeffrey W. Pollard (The Journal of Clinical Investigation, 2022)
Tumor-associated macrophages (TAMs) promote metastasis and tumor cell extravasation, survival, and growth. In hepatocellular carcinoma (HCC), the presence of TAM subpopulations correlates with poor outcome. In this issue of the JCI, Ning et al. report on their use of cell culture, mouse models, and human data sets to investigate the interactions between aerobic glycolysis and carbonic anhydrase XII (CA12) expression in HCC. Aerobic glycolysis promoted CA12 upregulation in TAMs, which induced a protumoral phenotype to promote tumor growth and metastasis. Tumor cell factors derived from HCC samples induced CA12 upregulation in tumor-infiltrating TAMs via the HIF1α pathway. In preclinical models of HCC, CA12 inhibition reduced tumor growth and lung metastasis and reduced TAM infiltrate. Notably, dual treatment with anti-PD1 and CA12 inhibitors synergistically attenuated tumor growth and metastasis and enhanced survival compared with either treatment alone. These findings suggest that targeting CA12 in combination with immune-checkpoint blockade may provide treatment options for HCC.